Acceptance of learning vocabulary via mobile-assisted language learning among community college of Qatar foundation students: Quizlet as a tool - Mohamed, Baraa Ahmed Shiekh; Salam, Abdul Rahim; Alwahoub, Husam Masaoud (Indonesian Journal of Applied Linguistics, 2024)
Integrating mobile devices into language learning has transformed vocabulary acquisition by providing learners with flexibility and access to educational resources anytime, anywhere. Mobile-assisted Language Learning (MALL) capitalizes on the widespread use of smartphones and tablets, allowing learners to engage with vocabulary exercises in a more accessible way. Previous research highlights that learners perceive mobile devices as enjoyable tools, and their acceptance is crucial for successful educational implementation. However, limited research exists in the context of Qatar. This study explores the acceptance of MALL among foundation students at the Community College of Qatar, using Quizlet due to its variety of features for vocabulary learning. A qualitative methodology was employed, involving interviews and reflection forms from forty-one participants across four academic levels, with thematic analysis conducted using ATLAS.ti 9. The findings revealed that participants generally had positive attitudes toward mobile applications in education but emphasized the importance of balancing MALL with diverse teaching methods to avoid monotony. Although MALL fosters learner autonomy, challenges such as technical issues, academic dishonesty, and cognitive distraction were noted. Despite these concerns, the study suggests that with proper administrative and educational interventions, these challenges can be mitigated, making vocabulary learning through MALL more effective, engaging, and acceptable to students at the Community College of Qatar.